Analysis of surface cracks in round bars using dual boundary element method - Ramezani, Mohammadkazem; Purbolaksono, Judha; Andriyana, Andri; Ramesh, Singh; Mardi, Noor Azizi (Elsevier, 2018)
A closed-form solution for stress intensity factors (SIFs) of a semi-elliptical surface crack in round bars subjected to torsional loading using the dual boundary element method are presented in this paper. The SIFs of surface cracks having different crack aspect ratios and inclination angles were calculated using the numerical software BEASY. In general, the results revealed that the Mode III SIF was strongly affected by both the crack size and crack shape whereas that crack aspect ratio had the greatest influence on the SIFs regardless of the fracture modes.